ARE MALE PUPILS OBESE? - Borislav Obradović; Biljana Srdić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
There are many facts that make it necessary to have a thorough look at the subject of childhood obesity. The dramatic rise in the prevalence of obesity in European countries and the USA has become a major health concern. Setting: A Serbian kindergarten. Subjects: A total of 490 boys aged 8-11 years at baseline. Methods: For each child accurate weights and height measurements were obtained. BMI was than calculated and plotted on the appropriate growth chart (based on the age and gender). Finally, the plotted measurements were interpreted and compared. Results: Most of the subjects at the age of 8, 9, 10 and 11 years considered to have a normal body weight, N=71, 65.1%; N=96, 72.7%; N=89, 69.5%; N=89, 73.6%, respectively. Underweight was confi rmed among the least number of subjects (N=2, 1.8%; N=2, 1.5%; N=11, 8.6%; N=5, 4.1%). Overweight was determined at 7-11% of all boys at the age of 8-11 years. Finally, risk of overweight was confi rmed in 11.6-22.0% of cases of all years of age. Discussion: Even though most subjects considered having normal body weight, there is a big concern regarding 7-11% of over weighted boys as well as 11.6-22.0% at the risk of overweight. Despite the fact that children 7-11 years from Serbia and Montenegro in the prevalence of overweight and obesity hold sixth place out of 20 [4], these results should call for action.